2021
DOI: 10.1016/j.isci.2021.102061
|View full text |Cite
|
Sign up to set email alerts
|

Early death of ALS-linked CHCHD10-R15L transgenic mice with central nervous system, skeletal muscle, and cardiac pathology

Abstract: Mutations in coiled-coil-helix-coiled-coil-helix domain containing 10 (CHCHD10) have been identified in patients suffering from various degenerative diseases including mitochondrial myopathy, spinal muscular atrophy Jokela type, frontotemporal dementia, and/or amyotrophic lateral sclerosis (ALS). The pathogenic mechanism underlying CHCHD10-linked divergent disorders remains largely unknown. Here we show that transgenic mice overexpressing an ALS-linked CHCHD10 p.R15L mutation leads to an abbreviated lifespan c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…As mammals express both CHCHD2 and CHCHD10, genetic loss of either gene produces subtle to no phenotype (Burstein et al, 2018;Liu Y.T. et al, 2020;Ryan et al, 2021;Sato et al, 2021), likely due to redundancy and compensation. However, it was recently reported that CHCHD2 −/− mice show p62 inclusion formation and dopaminergic neuronal loss in an age-dependent manner (Sato et al, 2021).…”
Section: Mouse Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mammals express both CHCHD2 and CHCHD10, genetic loss of either gene produces subtle to no phenotype (Burstein et al, 2018;Liu Y.T. et al, 2020;Ryan et al, 2021;Sato et al, 2021), likely due to redundancy and compensation. However, it was recently reported that CHCHD2 −/− mice show p62 inclusion formation and dopaminergic neuronal loss in an age-dependent manner (Sato et al, 2021).…”
Section: Mouse Modelsmentioning
confidence: 99%
“…Interestingly, CHCHD10 R15L transgenic mice die from cardiac failure because of the degeneration of cardiomyocytes. Despite these pathologies, CHCHD10 R15L transgenic mice do not exhibit paralysis or abnormal motor phenotypes (Ryan et al, 2021). Perhaps the divergent disease phenotypes between CHCHD2 mutations and CHCHD10 mutations may in part be explained by their ability to associate with different pathological proteins such as α-synuclein (Ikeda et al, 2019;Imai et al, 2019a) and TDP-43 (Woo et al, 2017;Genin et al, 2019;, respectively, the latter of which is a pathological hallmark of FTD-ALS (Neumann et al, 2006).…”
Section: Toward Understanding the Divergent Functions Of Chchd2 And Chchd10mentioning
confidence: 99%
See 1 more Smart Citation
“…CHCHD19 S55L knock-in mice were developed by two other independent groups [400,401]. Recently, Ryan and collaborators [402] generated transgenic mice overexpressing CHCHD10 R15L , which showed transgene copy-linked abbreviated lifespan compared with mice over expressing WT CHCHD10. However, CHCHD10 R15L mice performed comparably to control mice in motor behavioral tasks, without developing paralysis.…”
Section: Chchd10 Mutationsmentioning
confidence: 99%
“…CHCHD10 encodes a mitochondrial protein, which may maintain the MICOS ( Genin et al, 2016 ). Mutant CHCHD10 is associated with mitochondrial dysfunction and the early death of motor neurons ( Ryan et al, 2021 ). In mutant CHCHD10 ALS mice, aggregation of mutant CHCHD10 induces proteotoxic stress and the upregulation of the UPR mt transcriptional regulators ATF5 and CHOP ( Anderson et al, 2019 ).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%